Design of a combined lens for rectangular illumination. (January 2020) - Zhu, Z; Peng, B; Yuan, J; Xu, X
Rectangular illumination has found extensive application in the field of LED lighting. In this paper, a design method for a combined lens has used the two characteristics of refraction and diffuse reflection for rectangular illumination. The combined lens is composed of a cutting lens and a pedestal. We determined the cutting lens through the shape of the target plane and then applied diffuse reflection material to the partial surface of the pedestal. The diffuse reflection material is used to improve the lighting efficiency of the target plane. The surface of the pedestal is obtained by lofting from the contour of the cutting lens to the contour of plane where the light source is placed. Based on this method, the combined lens is designed for rectangular illumination. The result shows that the performance of the target plane meets the requirements of rectangular lighting. The uniformity is about 88% and the lighting efficiency is improved to 75%.